The biology of soil a community and ecosystem approach - Bardgett, Richard D. (Oxford : Oxford University Press, 2005)
Soil science has undergone a renaissance with increasing awareness of the importance of soil organisms & below-ground biotic interactions as drivers of community & ecosystem properties.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Soil biology